Возраст литосферного источника вендских траппов Волыни - Шумлянский, Л.В.; Носова, А.А. (Видавничий дім "Академперіодика" НАН України, 2008)
The paper deals with comparison of the Sm−Nd model ages of the whole-rock samples of Vendian (ca. 550 Ma) continental flood basalts of the Volyn region and 207Pb/206Pb ages of zircons isolated from basalts. Sm−Nd model ages vary between 2050 and 1090 Ma with two spikes at 1500–1700 and ca. 2000 Ma. 207Pb/206Pb zircon ages form four groups: ca. 2000, 1820, 1470 Ma, and (549 ± 29) Ma. The former age corresponds to the time of basalt eruption. Sm−Nd model and 207Pb/206Pb zircon ages reveal good correspondence to the age of crust formation and stabilization of the lithospheric mantle in the western (svecofenian) part of the East-European craton and evidence about a significant role of the lithospheric source. Role of the plume material was impaired but increased drastically at the latest stages of magmatism.